PEMAHAMAN GURU TENTANG EVALUASI PEMBELAJARAN ANAK USIA DINI - Oktavia Ramadhani; Tri Atuti Handayani; Rizki Mustikasari (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2026)
This study aims to examine teachers’ understanding of diagnostic, formative, and summative evaluation in early childhood education and its relationship with classroom assessment practices. The study is motivated by the gap between the ideal concept of learning evaluation and its implementation in early childhood education settings, which remains insufficiently integrated.This research employed a qualitative approach with a descriptive design, conducted at RA Al Aziziyah Kismantoro and TK Kemala Bhayangkari 61 Pulung during the first semester of the 2025/2026 academic year. Data were collected through in-depth interviews, classroom observations, and document analysis, and were analyzed using the interactive model of Miles and Huberman.The findings reveal that teachers’ understanding of the three types of evaluation is uneven and demonstrates distinct characteristics. Diagnostic evaluation is conducted implicitly without systematic documentation, formative evaluation is implemented regularly but not optimally utilized for instructional improvement, while summative evaluation tends to focus on narrative reporting with limitations in objectivity. This study contributes to clarifying the gap between conceptual understanding and practical implementation of learning evaluation in early childhood education, while emphasizing the importance of systematically integrating diagnostic, formative, and summative evaluations. The implications highlight the need for strengthening teachers’ capacity, developing practical evaluation documentation systems, and providing institutional policy support to improve the quality of assessment practices in early childhood education.